The efficiency of equity - Stephan Klasen (Georg-August-Universität Göttingen, Ibero-America Institute for Economic Research (IAI), 2006)
In standard neo-classical economics, efficiency and equity issues are largely treated as separate and separable issues. In this paper, I will discuss findings from four strands of literature that challenge this separability and in fact suggest that greater equity will promote greater efficiency in the sense of maximizing well-being in a society. There four strands refer to findings from the experimental literature on the importance of equity or fairness, the subjective well-being literature on the importance of relative incomes and inequality on subjective well-being, the distribution-adjusted well-being literature that combines measures of mean incomes with measures of income inequality to derive at welfare judgements across space and time, and the literature on the relationship between income and gender inequality on economic growth. Some implications for research and policy are explored.
Keywords: I31; D5; C9; 330